Penerapan Membaca Intensif dengan Kemampuan Menemukan Paragraf Deduktif dan Paragraf Induktif: Implementation of Intensive Reading with the Ability to Find Deductive Paragraphs and Inductive Paragraphs - Siregar, Harumi (ITScience (Information Technology and Science), 2024)
The ability of students to find deductive and inductive paragraphs is still low, which is caused by inappropriate learning methods and limited intensive reading time allocation. This study aims to determine the relationship between intensive reading ability and the ability to find deductive and inductive paragraphs in grade XI students of SMA Dharma Pancasila Medan. This study uses a quantitative correlation method with statistical analysis. The results of the study showed a significant relationship between intensive reading ability and the ability to find deductive and inductive paragraphs. The majority of respondents have sufficient intensive reading ability, as many as 16 people (51.6%), and the ability to find deductive and inductive paragraphs is also quite good, as many as 24 people (77.4%). The correlation coefficient value found was 0.498, greater than rtable of 0.355, with a significance of 0.004 which is smaller than the probability value of 0.05. In addition, the tcount value of 3.096 is greater than ttable of 2.045. Based on the analysis, it can be concluded that grade XI students of SMA Dharma Pancasila Medan generally have quite good intensive reading ability. The relationship between intensive reading ability and the ability to find deductive and inductive paragraphs is also significant. This study confirms that efforts to improve intensive reading ability can have a positive impact on students' ability to find deductive and inductive paragraphs.